TINJAUAN KOREOGRAFI TARI PODANG DI KELURAHAN BULAKAN BALAI KANDI KECAMATAN PAYAKUMBUH BARAT KOTA PAYAKUMBUH - Desi Lilianti Akhirta; Afifah Asriati; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2015)
Abstract This article aims to describe Choreography Podang in rural village hall Kandi West Payakumbuh Payakumbuh. This type of research is a qualitative descriptive method of analysis. The object of this study is Podang Dance in the Village Hall Kandi West Payakumbuh Payakumbuh. The main instrument is the researchers themselves. Data collection techniques such as literature, observation, interviews and documentation. Data analysis technique is a way to sort the data according to the choreography Podang then describe the data according to the issues discussed. The results showed that: the elements of choreography in dance Podang there is motion, floor design, music, top design, which includes the design of the angle, contrast, low, high and flat, the design of which is the dominant angular design, design dramatically the dance Podang the cone ganda.koreografi on dance podang the composition of the groups small. Theme dance Podang the courage and spirit of the high life. Costume on the dance Podang loose black shirt, black, black pants galembong, jao gloves and headband black (headband). Keywords: Review, choreography and dance Podang,